COMMUNICATION CONFLICT MANAGEMENT OF HINDU–BUDDHIST COMMUNITIES IN STRENGTHENING RELIGIOUS MODERATION IN TULUK BIU AND BATUR VILLAGES - Bagus Ade Tegar Prabawa; Adisastra, I Nyoma Surpa (International Journal of Social Studies, 2025)
The increasing social pressures of modernization, tourism, and globalization have posed significant challenges to interreligious harmony in multicultural regions such as Bali. Within this context, the present study on communication conflict management among Hindu–Buddhist communities in Tuluk Biu and Batur Villages, Kintamani, Bangli becomes both relevant and urgent. The research aims to understand how interfaith communication patterns rooted in local cultural and spiritual values strengthen religious moderation while offering a contextually grounded model of peaceful communication in Balinese society. The main objective is to analyze communication patterns, the role of traditional and governmental institutions, and the spiritual foundations that sustain harmonious Hindu–Buddhist relations at the community level. This study employed a qualitative descriptive approach, conducted in Tuluk Biu and Batur Villages, Kintamani District, Bangli Regency. The key informants included the village head, traditional leaders (Bendesa Adat), Hindu religious leaders, and Buddhist monks. Data were collected through observation, in-depth interviews, and literature studies, and then analyzed thematically and interpretatively using the theoretical frameworks of Communication Conflict Management, Transformative Communication, and the Balinese ethical philosophy of Tri Hita Karana. The findings reveal that the Hindu–Buddhist communities in Kintamani have developed collaborative, empathetic, and transformative communication practices. Spiritual values such as tat twam asi (“I am you”), karuna (compassion), and ahimsa (non-violence) serve as ethical foundations for peaceful dialogue, while traditional institutions and village governance act as mediators maintaining social equilibrium. Cultural elements such as menyama braya (brotherhood) and the banjar system strengthen community-based interfaith cooperation. These results demonstrate that harmony among religious groups arises organically from locally embedded spiritual and cultural communication practices rather than external interventions. In conclusion, the Hindu–Buddhist communication model in Kintamani contributes theoretically by expanding conflict management and intercultural communication paradigms toward a spirituality-based approach. Practically, it offers an authentic, contextual, and sustainable model for fostering religious moderation in plural societies. Future studies are recommended to explore similar spiritual-communicative frameworks in other multireligious regions to support Indonesia’s national agenda on religious moderation.